Investigating Pore‐Opening of Hydrogel Foams at the Scale of Freestanding Thin Films. Issue 17 (4th July 2022) - Andrieux, Sébastien; Patil, Mayur; Jacomine, Leandro; Hourlier‐Fargette, Aurélie; Heitkam, Sascha; Drenckhan, Wiebke
Abstract: Controlling the pore connectivity of polymer foams is key for most of their applications, ranging from liquid uptake, mechanics, and acoustic/thermal insulation to tissue engineering. Despite their importance, the scientific phenomena governing the pore‐opening processes remain poorly understood, requiring tedious trial‐and‐error procedures for property optimization. This lack of understanding is partly explained by the high complexity of the different interrelated, multiscale processes which take place as the foam transforms from an initially fluid foam into a solid foam. To progress in this field, this work takes inspiration from long‐standing research on liquid foams and thin films to develop model experiments in a microfluidic "Thin Film Pressure Balance." These experiments allow the investigation of isolated thin films under well‐controlled environmental conditions reproducing those arising within a foam undergoing cross‐linking and drying. Using the example of alginate hydrogel films, the evolution of isolated thin films undergoing gelation and drying is correlated with the evolution of the rheological properties of the same alginate solution in bulk. The overall approach is introduced and a first set of results is presented to propose a starting point for the phenomenological description of the different types of pore‐opening processes and the classification of the resulting pore‐opening types. Abstract : This paper describes a novel method for the investigation of pore‐opening mechanisms in hydrogel foams. The experiment introduced here relies on the study of the thinning and rupture behavior of gelling freestanding thin films using a microfluidic thin‐film pressure balance.